Mesenteric cyst of descending colon: A rare subtype - Mahno, Noor Ezmas; Ong, David; Shabeeb, Fadeel; Md Nor, Azmi (2014)
Introduction: Mesenteric cyst is rare intra-abdominal lesions(1)(2) and account for only one in 100,000 acute adult admissions(1). It can occur at any age. Usually, it was found incidentally unless the cyst became complicated(2). Most common presenting symptoms are abdominal mass, distention, pain and vomiting(3). Although uncommon, complications such as infection, bleeding, torsion, rupture and intestinal obstruction may cause an acute abdomen(2). Mostly, it affected the mesentery of the small bowel. We are presenting 73 years old lady with incidental abdominal mass during medical checkup.